Repair of PCCP By The Gunnite Method - Elnakhat, Hassan A.M.; Hamdan, Adel (International Journal of Advanced Research in Engineering; Vol 1 No 2 (2015): International Journal of Advanced Research in EngineeringDO - 10.24178/ijare.2015.1.2.23, 2015)
Repair an affected pipes with mortar coating delaminating using the Gunnite method, where the method applied on the affected pipes which the surface area of affected Coating delaminating reach up to entire pipe body, this method applied on more than 480 affected pipes in Man-Made River Project in desert of Libya.